2015
DOI: 10.1002/zaac.201500549
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, Crystal Structures, Thermal and Photoluminescent Properties of Four Coordination Complexes with a Hetero­cyclic Thioether Carboxylate Ligand

Abstract: A series of transition metal coordination complexes, {[Cu(3‐Sptta)2]·1/2H2O}n (1), {[Cd(3‐Sptta)2]·1/2H2O}n (2), [Zn(3‐Sptta)2(H2O)4] (3), and [Co(3‐Sptta)2(H2O)4] (4) were synthesized under solvothermal and solvent evaporation conditions using the newly designed heterocyclic N/NS carboxylate ligand [2‐(3‐pyridyl)‐1,3,4‐thiadiazole‐5‐]‐thio‐acetate (3‐Sptta) as a main building block. Their structures were determined by single‐crystal X‐ray diffraction analyses and further characterized by elemental analyses an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…The functionalisation of 2-mercapto-5-methyl-1,3,4-thiadiazole (1) with α,ωdihalogenoalkanes was performed by applying the one-step procedure shown in Scheme Sulphur-containing ligands, on the other hand, have shown remarkable coordination properties [54][55][56][57][58][59][60][61] and have displayed a wide range of applications [62][63][64][65][66][67][68]. Among them, heterocyclic thioethers have exhibited a broad spectrum of bioactivities [69][70][71][72] and efficiency as adsorbents for lead ion removal from water [73], ligands in N-heterocyclic carbene (NHC) complexes [74][75][76][77], metal-organic frame-works [78][79][80][81][82], etc. As a very particular example, it is shown that symmetrical bis-1,3,4-thiadiazole-containing bis-thioethers tune the framework formation of silver(I) coordination architectures [83].…”
Section: Resultsmentioning
confidence: 99%
“…The functionalisation of 2-mercapto-5-methyl-1,3,4-thiadiazole (1) with α,ωdihalogenoalkanes was performed by applying the one-step procedure shown in Scheme Sulphur-containing ligands, on the other hand, have shown remarkable coordination properties [54][55][56][57][58][59][60][61] and have displayed a wide range of applications [62][63][64][65][66][67][68]. Among them, heterocyclic thioethers have exhibited a broad spectrum of bioactivities [69][70][71][72] and efficiency as adsorbents for lead ion removal from water [73], ligands in N-heterocyclic carbene (NHC) complexes [74][75][76][77], metal-organic frame-works [78][79][80][81][82], etc. As a very particular example, it is shown that symmetrical bis-1,3,4-thiadiazole-containing bis-thioethers tune the framework formation of silver(I) coordination architectures [83].…”
Section: Resultsmentioning
confidence: 99%
“…Lanthanide-pyridinecarboxylic (picolinic) acid complexes are important to develop advanced luminescent materials with applications in photoelectronics, laser, luminescence labels, fluorescent probes, luminescence sensors, light-conversion molecular devices (LCMDs), organic light-emitting devices (OLEDs), fluorescent lamps, and cathode-ray tubes as well as plasma display panels (PDPs). Lanthanide-aromatic carboxylate complexes display interesting photophysical properties due to the antenna effect; that is, the organic ligand in the complex absorbs energy more intensely than the isolated organic ligand . However, these complexes exhibit low thermal and chemical stabilities.…”
Section: Introductionmentioning
confidence: 99%